Gamification and Interactive Learning: Enhancing Students Engagement and Proficiency Outcomes - Rabi'ah; Yoyok Hadiwinarso; Jannah, Raudlatul (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This research investigates the effectiveness of gamification and interactive learning strategies in enhancing student engagement and language acquisition, addressing a critical gap in empirical evidence regarding their impact on motivation and achievement among language learners. Employing a qualitative approach, this study collected data through interview and classroom observations to know the students responses in using innovative method like gamification. The findings reveal that gamified elements, such as point scoring, competition, and interactive tasks, significantly boost student motivation and participation, leading to measurable improvements in language proficiency compared to traditional instructional methods. Furthermore, qualitative feedback from participants reveals that these tactics promote a more dynamic and supportive learning environment, which benefits both educators and students. Finally, the implications of this study advocate for the integration of gamification in language education curricula, suggesting that enhancing engagement through innovative teaching methods can foster greater language competency and readiness for communication challenges, influencing educational practices and policies in the field.